DNA methylation mutants in Physcomitrella patens elucidate individual roles of CG and non-CG methylation in genome regulation - Domb, Katherine (Proc Natl Acad Sci U S A, 2020)
Cytosine (DNA) methylation in plants regulates the expression of genes and transposons. While methylation in plant genomes occurs at CG, CHG, and CHH sequence contexts, the comparative roles of the individual methylation contexts remain elusive. Here, we present Physcomitrella patens as the second plant system, besides Arabidopsis thaliana, with viable mutants with an essentially complete loss of methylation in the CG and non-CG contexts. In contrast to A. thaliana, P. patens has more robust CHH methylation, similar CG and CHG methylation levels, and minimal cross-talk between CG and non-CG methylation, making it possible to study context-specific effects independently. Our data found CHH methylation to act in redundancy with symmetric methylation in silencing transposons and to regulate the expression of CG/CHG-depleted transposons. Specific elimination of CG methylation did not dysregulate transposons or genes. In contrast, exclusive removal of non-CG methylation massively up-regulated transposons and genes. In addition, comparing two exclusively but equally CG- or CHG-methylated genomes, we show that CHG methylation acts as a greater transcriptional regulator than CG methylation. These results disentangle the transcriptional roles of CG and non-CG, as well as symmetric and asymmetric methylation in a plant genome, and point to the crucial role of non-CG methylation in genome regulation.